Beyond the Village Gate: Commercializing Smallholder Agriculture in Indonesia - Fauzan, Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2024)
The commercialization of smallholder agriculture emerges as a pivotal strategy for enhancing productivity, income, and food security in developing countries, including Indonesia. This article systematically reviews scientific literature and policy documents to analyze the dynamics, challenges, and strategies related to the commercialization of smallholder farmers in Indonesia. Drawing from over 40 relevant academic and institutional sources, the review identifies that various multidimensional factor, such as market access, agricultural inputs, farmer institutions, infrastructure, and policy support, shape the commercialization process. Although commercialization has considerable potential to enhance farmer welfare, it also poses risks, including the marginalization of poor farmers and the potential for natural resource exploitation if not managed inclusively. Empirical evidence reveals that smallholder farmers effectively accessing commercial markets can experience income increases ranging from 20% to 40% compared to their subsistence counterparts. This article advocates strengthening farmer institutions, investing in supportive infrastructure, ensuring access to financing, and implementing region-specific policies focused on superior commodities. Ultimately, these findings aim to inform the formulation of equitable and sustainable policies that facilitate the transformation of smallholder agriculture in Indonesia.